2021
DOI: 10.1111/nph.17264
|View full text |Cite
|
Sign up to set email alerts
|

Localised laccase activity modulates distribution of lignin polymers in gymnosperm compression wood

Abstract: Summary The woody stems of coniferous gymnosperms produce specialised compression wood to adjust the stem growth orientation in response to gravitropic stimulation. During this process, tracheids develop a compression‐wood‐specific S2L cell wall layer with lignins highly enriched with p‐hydroxyphenyl (H)‐type units derived from H‐type monolignol, whereas lignins produced in the cell walls of normal wood tracheids are exclusively composed of guaiacyl (G)‐type units from G‐type monolignol with a trace amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 74 publications
1
27
0
Order By: Relevance
“…The cluster with LAC paralogs known to oxidise flavonoids had the smallest binding pockets with moderate (AtLAC15) to minimal (ADE/LAC) compactness and pocket mouth areas (Figure 7E). Another cluster grouped paralogs pivotal for vascular lignification (AtLAC4 and AtLAC11) as well as CoLAC1 shown to preferentially oxidise lignin hydroxyphenyl (H) residue precursors of lignin (Hiraide et al, 2021). This group presented intermediate sized binding pockets of generally low compactness gated by mostly small mouth area (Figure 7E).…”
Section: Modelling the Structural Differences Between Laccase Paralogsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cluster with LAC paralogs known to oxidise flavonoids had the smallest binding pockets with moderate (AtLAC15) to minimal (ADE/LAC) compactness and pocket mouth areas (Figure 7E). Another cluster grouped paralogs pivotal for vascular lignification (AtLAC4 and AtLAC11) as well as CoLAC1 shown to preferentially oxidise lignin hydroxyphenyl (H) residue precursors of lignin (Hiraide et al, 2021). This group presented intermediate sized binding pockets of generally low compactness gated by mostly small mouth area (Figure 7E).…”
Section: Modelling the Structural Differences Between Laccase Paralogsmentioning
confidence: 99%
“…Other LAC paralogs such as AtLAC1, 3, 5, and 13 also specifically accumulate in the casparian strip of endodermal cells (Rojas-Murcia et al, 2020). In Chamaecyparis obtusa, CoLAC1 and CoLAC3 were respectively localised in the inner and outer S2 layers of tracheid compression wood (Hiraide et al, 2021). Beside cell wall localisation, LACs can be targeted to vacuoles in litchi (Fang et al, 2015), to the cytoplasm in hairy roots of Brassica juncea (Telke et al, 2011), but are also predicted to mitochondria in Pinus taeda, Oryza sativa, and Gossypium spp.…”
Section: Localisation and Expression Of Laccasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gymnosperms also produce a compression layer within xylem that enriched in H-lignin in tracheid. A recent study showed that spatial patterning of H-and G-lignin during wood formation is related to different localizations and enzyme activities of lignin polymerization enzymes, laccases (Hiraide et al, 2021). Interestingly, some gymnosperm species, such as Gentales, can also synthesize S-lignin (Renault et al, 2019).…”
Section: G-lignin Biosynthesis In Gymnospermsmentioning
confidence: 99%
“…Due to the low spatial resolution, standard lignin analyses have led to consider lignin polymerisation as a random process only regulated by monomer supply (Barros et al 2015). However, recent works challenged this model by showing that lignification is a genetically controlled process regulating the amounts, linkages and composition of lignin in each cell type and their different cell wall layers Blaschek, Champagne, et al 2020;Yamamoto et al 2020;Hiraide et al 2021). Indeed, different TE morphotypes have been shown to contain lignins with different amounts and differently positioned G CHO (Blaschek, Champagne, et al 2020;Yamamoto et al 2020).…”
Section: Introductionmentioning
confidence: 99%